2011
DOI: 10.1093/cercor/bhr100
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Visual Word Form Area Is Functionally Connected to the Dorsal Attention Network

Abstract: The putative visual word form area (pVWFA) is the most consistently activated region in single word reading studies (i.e., Vigneau et al. 2006), yet its function remains a matter of debate. The pVWFA may be predominantly used in reading or it could be a more general visual processor used in reading but also in other visual tasks. Here, resting-state functional connectivity magnetic resonance imaging (rs-fcMRI) is used to characterize the functional relationships of the pVWFA to help adjudicate between these po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
152
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(195 citation statements)
references
References 90 publications
32
152
5
Order By: Relevance
“…Specifically, left SPL, and unexpectedly left lateral IPS, displayed increased functional connectivity with areas of occipotemporal cortex (including the putative visual word-form area and lateral occipital cortex) during uncertain relative to certain decisions. At least for the SPL, this result complements those from a recent study which reported resting-state functional connectivity between SPL and the visual word-form area (Vogel et al, 2012), suggesting that uncertain decisions might engage pathways that are otherwise intrinsically connected.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, left SPL, and unexpectedly left lateral IPS, displayed increased functional connectivity with areas of occipotemporal cortex (including the putative visual word-form area and lateral occipital cortex) during uncertain relative to certain decisions. At least for the SPL, this result complements those from a recent study which reported resting-state functional connectivity between SPL and the visual word-form area (Vogel et al, 2012), suggesting that uncertain decisions might engage pathways that are otherwise intrinsically connected.…”
Section: Discussionsupporting
confidence: 84%
“…However, some studies that have applied network analyses to resting functional connectivity have not found evidence for a dedicated reading network (Vogel et al 2012(Vogel et al , 2013. Regions involved in reading are members of default-mode, visual, motor, and fronto-parietal networks (Vogel et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The network corresponding to the orange/ SMG cluster included bilateral intraparietal sulcus, anterior insula, and dorsal prefrontal regions, consistent with the dorsal attention or fronto-parietal network (DAN; Power et al [2011]). This network also included a bilateral occipito-temporal region that has been associated with orthographic processing (McCandliss et al 2003), but recent work suggests that it is also integrated with the DAN at rest (Vogel et al 2012). This network was anticorrelated with posterior cingulate, medial prefrontal, and anterior caudate regions (shown in blue).…”
Section: Tpj Clustering: 3-cluster Solutionmentioning
confidence: 99%
“…Moreover, vWFA has been shown to have resting-state functional correlations with regions in the dorsal attention network (left and right aIPS, MT?, and FEF regions) with minimal or absent correlations with reading-related regions. These dorsal attention correlations were not a general property of all regions in the fusiform cortex (e.g., the FFA was not connected to the MT to which is very closely located) [54]. Thus, the impaired pattern of activation in this region may be associated with our patients' general simultaneous processing deficit.…”
Section: Discussionmentioning
confidence: 67%